(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Healthy soils are very vital for cultivation of crops. This study therefore assessed chemical health attributes of agricultural soils in Abia State, southeastern Nigeria. Surface soil samples were collected randomly at depths of 0-20cm using free survey technique from three communities namely; Isingwa, Ngwaukwu and Ntigha. Soil samples were collected and subjected to routine laboratory soil analyses. Data generated were analyzed using ANOVA and significant means separated using FLSD at 5% probability level. The chemical health statuses of the soils were determined using chemical soil health indicators given by USDA, (2006). These attributes were further subjected to the ranking scheme of Zakir et al., (2022) which ranked soils from 0 to 3 with soil health classes of healthy, sub-healthy, weak and degraded respectively comparing them with ratings of soil properties. Results showed that the CaCO3 content of the study area were ranked 2 generally and considered weak. For ECEC, the soils of Isingwa and Ngwaukwu were degraded and ranked as 3 but Ntigha was ranked 2 and rated weak. For sodium saturation, the soils were healthy and ranked 0. In respect to pH, the soils in all study locations were weak generally and ranked 2. The soils were generally ranked 2 and rated weak with respect to soil organic matter. The overall ranking of the chemical attributes of the study area was 2 indicating that the soils were generally weak in chemical health. Regenerative agriculture is therefore recommended for the study area.